2009
DOI: 10.1103/physrevb.79.235132
|View full text |Cite
|
Sign up to set email alerts
|

Transport in disordered graphene nanoribbons

Abstract: We study electronic transport in graphene nanoribbons with rough edges. We first consider a model of weak disorder that corresponds to an armchair ribbon whose width randomly changes by a single unit cell size. We find that in this case, the low-temperature conductivity is governed by an effective one-dimensional hopping between segments of distinct band structure. We then provide numerical evidence and qualitative arguments that similar behavior also occurs in the limit of strong uncorrelated boundary disorde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…The basic idea is to start from a tight-binding Hamiltonian for a clean and regular ribbon (in general with hydrogen passivation on the edges), and then adding [37] or removing [36, 139 141] carbon atoms at the edges, or varying the width of the system [142] to account for roughness, or introducing Anderson disorder [143]. The most proper way of adding/removing atoms at the edges avoids fi nal confi gurations that might cause steric problems.…”
Section: Nano Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea is to start from a tight-binding Hamiltonian for a clean and regular ribbon (in general with hydrogen passivation on the edges), and then adding [37] or removing [36, 139 141] carbon atoms at the edges, or varying the width of the system [142] to account for roughness, or introducing Anderson disorder [143]. The most proper way of adding/removing atoms at the edges avoids fi nal confi gurations that might cause steric problems.…”
Section: Nano Researchmentioning
confidence: 99%
“…The effect of sequences of large conducting and semiconductor armchair fragments has been investigated in detail by Martin et al [142]. The length of each metallic fragment is such as to preserve the band structure of the corresponding Nano Res (2008) 1: 361 394 Nano Research least for wide ribbons.…”
Section: Nano Researchmentioning
confidence: 99%
“…[6][7][8]). It was found that already very modest edge disorder is sufficient to induce the conduction energy gap in the otherwise metallic nanoribbons and to lift any difference in the conductance between nanoribbons of different edge geometry, suggesting that this type of disorder can be very important for altering other fundamental characteristics of GHRs.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30] In particular, such calculations confirmed the essential contribution to conductivity from the edge states provided that the intervalley coupling due to scattering from impurities is absent. [25][26][27] Besides, the localization corrections to the conductivity in disordered graphene nanoribbons have been studied by Lherbier et al 28 and Mucciolo et al 29 They found that the edges essentially affect the disorder-induced corrections.…”
Section: Introductionmentioning
confidence: 62%
“…The role of randomly fluctuating width of the nanoribbon has been also studied numerically by Martin and Blanter. 30 In their model, the low-temperature conductivity can be governed by electron hoppings between some segments of the ribbon.…”
Section: Introductionmentioning
confidence: 99%